2017
DOI: 10.1038/ajg.2017.394
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical Rates for Crohn’s Disease are Decreasing: A Population-Based Time Trend Analysis and Validation Study

Abstract: Objectives:Temporal changes for intestinal resections for Crohn’s disease (CD) are controversial. We validated administrative database codes for CD diagnosis and surgery in hospitalized patients and then evaluated temporal trends in CD surgical resection rates.Methods:First, we validated International Classification of Disease (ICD)-10-CM coding for CD diagnosis in hospitalized patients and Canadian Classification of Health Intervention coding for surgical resections. Second, we used these validated codes to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 34 publications
7
111
1
2
Order By: Relevance
“…The overall decrease in surgical stoma‐formation rates mirrors observations that rates of surgical resections in CD may be on the decline , as may rates of colectomy for ulcerative colitis . A previous study from our unit demonstrated that reductions in overall intestinal resection rates in CD were also attributable to a decrease in emergency procedures: from 2002 to 2010, emergency bowel resections decreased by 10.1% (95% CI: −13.4 to −6.7) per year . However, our finding that rates of permanent stoma formation in CD have remained stable contrasts the results of a previous study by Coscia et al .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The overall decrease in surgical stoma‐formation rates mirrors observations that rates of surgical resections in CD may be on the decline , as may rates of colectomy for ulcerative colitis . A previous study from our unit demonstrated that reductions in overall intestinal resection rates in CD were also attributable to a decrease in emergency procedures: from 2002 to 2010, emergency bowel resections decreased by 10.1% (95% CI: −13.4 to −6.7) per year . However, our finding that rates of permanent stoma formation in CD have remained stable contrasts the results of a previous study by Coscia et al .…”
Section: Discussionsupporting
confidence: 76%
“…In this population-based study, we demonstrated that both emergency and temporary stomaformation rates in CD have decreased, although this has not been paralleled by a change in the rate of permanent stoma formation. The overall decrease in surgical stoma-formation rates mirrors observations that rates of surgical resections in CD may be on the decline [3,4,18,19], as may rates of colectomy for ulcerative colitis [20]. A previous study from our unit demonstrated that reductions in overall intestinal resection rates in CD were also attributable to a decrease in emergency procedures: from 2002 to 2010, emergency bowel resections decreased by 10.1% (95% CI: À13.4 to À6.7) per year [4].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We additionally reported these estimates and their trends by age group (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), 50-69 and ≥70 years old) and sex. We investigated the burden of IBD by geographic macro-regions and quintiles of socio-demographic index (SDI).…”
Section: Me Thodsmentioning
confidence: 99%
“…Globally, between 1990 and 2017, the prevalence of IBD in children Low-middle SDI L ow SDI mortality. 10,11 Several studies have also reported decreasing trends for colectomy in ulcerative colitis (UC), 12,13 Crohn's disease (CD) 14,15 and overall IBD. 16 These findings suggest significant improvements in preventing the most severe outcomes associated with disease progression.…”
Section: Ibd In Childrenmentioning
confidence: 99%